England, Englishness and Brexit. Issue 2 (25th May 2016) - Henderson, Ailsa; Jeffery, Charlie; Liñeira, Robert; Scully, Roger; Wincott, Daniel; Wyn Jones, Richard
Abstract: In the 1975 referendum England provided the strongest support for European integration, with a much smaller margin for membership in Scotland and Northern Ireland. By 2015 the rank order of 'national' attitudes to European integration had reversed. Now, England is the UK's most eurosceptic nation and may vote 'Leave', while Scotland seems set to generate a clear margin for 'Remain'. The UK as a whole is a Brexit marginal. To understand the campaign, we need to make sense of the dynamics of public attitudes in each nation. We take an 'archaeological' approach to a limited evidence‐base, to trace the development of attitudes to Europe in England since 1975. We find evidence of a link between English nationalism and euroscepticism. Whatever the result in 2016, contrasting outcomes in England and Scotland will exacerbate tensions in the UK's territorial constitution and could lead to the break‐up of Britain.